2020
DOI: 10.1016/j.talanta.2019.120392
|View full text |Cite
|
Sign up to set email alerts
|

Analytical possibilities of Putrescine and Cadaverine enzymatic colorimetric determination in tuna based on diamine oxidase: A critical study of the use of ABTS

Abstract: The joint determination of putrescine (Put) and cadaverine (Cad) in the presence of other biogenic amines is studied using their enzymatic reaction with diamine oxidase (DAO). Three alternative methods are studied based on the intrinsic colorimetric properties of DAO or horseradish peroxidase (HRP), and the use of 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS) colorimetric reagent, respectively. In this last case an in-depth study is carried out in order to explain and solve some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…Finally, an oxidative half reaction completes the catalytic cycle by re-oxidizing the FAD with molecular oxygen and producing hydrogen peroxide. The possibility that metal ions may act as substrates for enzymes has recently been verified [32], which reinforces the hypothesis that the active center of the enzyme may be responsible for the formation of AuNPs. If so, after the LAAO-l-Phe enzymatic reaction, the catalytic center of the reduced enzyme would be regenerated by the Au(III) salt, which would be reduced to Au 0 , producing the reoxidation of the active center of the enzyme.…”
Section: Mechanism Of the Laao-l-phe Enzyme Reaction In The Presence Of Au(iii)supporting
confidence: 67%
“…Finally, an oxidative half reaction completes the catalytic cycle by re-oxidizing the FAD with molecular oxygen and producing hydrogen peroxide. The possibility that metal ions may act as substrates for enzymes has recently been verified [32], which reinforces the hypothesis that the active center of the enzyme may be responsible for the formation of AuNPs. If so, after the LAAO-l-Phe enzymatic reaction, the catalytic center of the reduced enzyme would be regenerated by the Au(III) salt, which would be reduced to Au 0 , producing the reoxidation of the active center of the enzyme.…”
Section: Mechanism Of the Laao-l-phe Enzyme Reaction In The Presence Of Au(iii)supporting
confidence: 67%
“…The EuDPA concentration was optimized as follows: 1 mL of OPI solution (5 mg mL −1 ) was added to varying amounts of EuDPA (40,100,200,300, and 400 μL of EuDPA solution (1 mg mL −1 )), after which the volume of the solutions was made up to 4 mL with distilled water. We found that the quenching efficiency of the OPI-EuDPA complex was highest when 200 µL of Eu-DPA solution was added to the above mixture, with a fixed concentration of 14.5 ng mL −1 SPD and 13.8 ng mL −1 PUT solution, as shown in Fig.…”
Section: Photoluminescence Of Opi-eudpa Probementioning
confidence: 99%
“…For example, (i) R ox can react with the amino acids of the main reaction and HRP; (ii) R red can react with the product of the main reaction or other chemicals present in the sample; (iii) R ox is unstable (it suffers disproportionation). Also, HRP presents additional lateral reactions with the analyte or the product of the oxidase reaction [ 4 ].…”
Section: Introductionmentioning
confidence: 99%